Small for gestational age is a risk factor for thyroid dysfunction in preterm newborns - Chunhua Liu; Kaiyan Wang; Jizhong Guo; Jiru Chen; Mei Chen; Zhexi Xie; Pu Chen; Beiyan Wu; Niyang Lin (BMC, 2020)
Abstract Background Thyroid hormones play an important role in the normal growth and maturation of the central nervous system. However, few publications addressed the altered thyroid hormone levels in preterm small for gestational age (SGA) newborns. We hypothesized preterm SGA infants have higher thyroid-stimulating hormone (TSH) concentrations than appropriate for gestational age (AGA) ones within the normal range and an increased incidence of thyroid dysfunction. Methods The study was designed to compare thyroid hormone levels within the normal range and the incidence of thyroid dysfunction in the SGA and AGA groups to test the hypothesis. The medical records of all preterm infants admitted to the neonatal intensive care unit (NICU) at the First Affiliated Hospital of Shantou University Medical College, Shantou, China, between January 1, 2015 and December 31, 2018, were reviewed. Blood samples were collected between 72 and 96 h of life and analyzed with TSH, free thyroxine (FT4) and free triiodothyronine (FT3) assays. Thyroid function test (TFT) results, and neonatal demographic and clinical factors were analyzed to identify the associations between SGA birth and altered thyroid concentrations and thyroid dysfunction. Results TSH and FT4 concentrations were significantly higher in the SGA group than the AGA group ((3.74(interquartile range (IQR):2.28 ~ 6.18) vs. 3.01(IQR: 1.81 ~ 5.41) mU/L, p = 0.018), and (17.76 ± 3.94 vs. 17.42 ± 3.71 pmol/L, p = 0.371), respectively). The higher TSH levels were associated with being SGA or Z-score of birth weight (BW) for GA after adjusting for potential confounders ((β SGA  = 0.68 (95% confidence interval (CI) 0.15 ~ 1.21), p = 0.013) or (β Z-score  = − 0.25 (95%CI -0.48 ~ − 0.03), p = 0.028), respectively). However, we did not find a significant association between SGA birth and altered FT4 concentrations. Furthermore, compared with the AGA group, the SGA group presented an increased incidence of transient hypothyroxinemia with delayed TSH elevation (dTSHe), a higher percentage receiving levothyroxine (L-T4) therapy, and a higher rate of follow-up within the first 6 months of life. Conclusions Preterm SGA newborns had significantly higher TSH concentrations within the normal range and an increased incidence of thyroid dysfunction. The SGA newborns with these features should be closely followed up with periodical TFTs and endocrinologic evaluation.